A Rate-Dependent Probabilistic Model of Hysteresis - Rod Cross; Michael Grinfeld; Harbir Lamba (Mathematics)
Instead of modelling an economic agent by a hysteron, we suggest a fluid–mechanical notion of rate-dependent hysteretic agents based on the theory of Poisson counters. It leads to a simple representation of assemblies of such agents. We discuss the properties of the new version of hysteresis and its advantages over classical models of hysteresis in economics.